Reduplication; Noun Formation Pattern in Ternate Language a Morphophonemic Study - Do Subuh, Rahma; Duwila, Ety (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
The Ternate language is one of the non-Austronesian languages which has several unique characteristics, including the form of prefixes and possessive verbs that can only be differentiated based on the context of speech and the absence of inflexion. It will produce or find a pattern of rules from the formation of nouns in the Ternate language. Data were analyzed morphophonemically using structural theory to find out the forms of nouns in Ternate and the process of their formation The main aim of this research is to find rules for noun formation, and patterns in the Ternate language. The method in this research is descriptive qualitative with observation and interview data collection techniques as well as literature study as data sources. Meanwhile, data analysis was carried out through the identification and classification stages as well as analysis of the formation process as nouns. In conclusion that nouns are formed from verb and adjective classes by repeating and adding phonemes; these nouns have the meanings of actor, tool, place/locative, possession, rather, and abstract.